2021
DOI: 10.1016/j.artd.2021.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Depression and Anxiety on 90-day Readmission Rates After Total Hip and Knee Arthroplasty

Abstract: Background Patients undergoing total joint arthroplasty have higher rates of anxiety, depression or anxiety and depression than the general population and higher costs of care, which lead to higher levels of postoperative dissatisfaction and readmission rates. We evaluated the readmission rates of patients undergoing total hip or knee arthroplasty with diagnoses of anxiety, depression, or both. Methods Our hospital’s prospectively collected data from Michigan’s statewid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Beyond inferior patient-reported outcomes, patients with depression or anxiety who underwent orthopaedic surgeries also had higher rates of hospital readmissions and surgical complications. 23,26,40 They were also more likely to require revision surgery. 23 Because of these readmissions, complications, and revisions, patients with depression and anxiety exhibit increased health care utilization, resulting in greater costs.…”
Section: Pathophysiology and Musculoskeletal Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond inferior patient-reported outcomes, patients with depression or anxiety who underwent orthopaedic surgeries also had higher rates of hospital readmissions and surgical complications. 23,26,40 They were also more likely to require revision surgery. 23 Because of these readmissions, complications, and revisions, patients with depression and anxiety exhibit increased health care utilization, resulting in greater costs.…”
Section: Pathophysiology and Musculoskeletal Painmentioning
confidence: 99%
“…Depression and anxiety have been well-studied as factors that negatively predict the degree of surgical success in orthopaedics; however, investigations into the impacts of depression and anxiety in foot and ankle surgery are fewer and more recent than investigations focusing on other anatomical areas. Mental health disorders have been demonstrated to negatively affect surgical outcomes for a wide range of orthopaedic surgeries, including total hip and knee arthroplasties, 2,26,27,30,35,38,40,51,66,74 hip arthroscopy, 23,37,48,63,64 shoulder and elbow surgery, 43,67,71 and spine surgery. 10,47,62 The contributions of depression and anxiety to foot and ankle pain and the success of foot and ankle surgery have been more properly investigated in the past 5 years; however, they have not yet been summarized and critically analyzed in a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Kalogianni et al demonstrated that, in patients undergoing elective cardiac surgery, preoperative education delivered by nurses reduced anxiety and post-operative complications of patients, but it was not effective in reducing readmissions [ 23 ]. Given anxiety has been shown to undermine the influence of discharge planning in transplant patients [ 24 ], and patients with anxiety requiring medication has been shown to be significantly associated with increased rates of readmission in the orthopedic population [ 25 ], anxiety itself may mitigate any gain associated with Ph DC , and addressing anxiety as part of discharge care planning may be a first step to decreasing readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Amiri [23]. Given anxiety has been shown to undermine the influence of discharge planning in transplant patients [24], and patients with anxiety requiring medication has been shown to be significantly associated with increased rates of readmission in the orthopedic population [25], anxiety itself may mitigate any gain associated with Ph DC , and addressing anxiety as part of discharge care planning may be a first step to decreasing readmissions.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Mental and social health factors have been identified as potential contributors to persistent pain, dissatisfaction, and complication rates following total hip arthroplasty (THA) and total knee arthroplasty (TKA). [4][5][6][7][8] Previous investigations have suggested that up to 20% of patients are dissatisfied following primary TKA. 9 Depressive and anxiety disorders may also adversely affect satisfaction after THA and TKA.…”
Section: Introductionmentioning
confidence: 99%